ADMINISTRATIVE AND LEGAL BASIS OF THE FUNCTIONING OF THE ANTI-CORRUPTION COURT: FOREIGN EXPERIENCE AND DOMESTIC REALITIES - Yemelyanov, Volodymyr; Antonova, Liudmyla; Ivashova, Ljudmyla (Public Administration and Regional Development, 2022)
The purpose of the article is to study and summarize the administrative and legal foundations of the organization of anti-corruption courts in foreign countries in comparison with the relevant experience of Ukraine. The current arguments in favor of the creation of special anti-corruption courts and against it have been identified. The already well-established definition of "anti-corruption court" is given. The variability of ways of creating anti-corruption courts and their functioning is given. Four main models of the organizational structure of anti-corruption courts have been identified. The thematic experience of the creation, problems of formation and stages of development of the Anti-Corruption Court of the Philippines (Sandiganbayan Court) as the country of the first specialized anti-corruption court and Indonesia (Typicor Court) as one of the most successful anti-corruption court models. In comparison with foreign experience, the relevant domestic experience is analyzed, namely, the process of formation and the current situation of the Supreme Anti-Corruption Court of Ukraine are generalized. The basic principles and objective miscalculations of the Law of Ukraine "On the Supreme Anti-Corruption Court" have been studied. The issue of multifaceted training of judges of the Supreme Anti-Corruption Court of Ukraine was considered: five main areas of this training were identified. The positive and negative components of the idea of creating the International Anti-Corruption Court (IACC) are described, its main purpose and overriding tasks are determined, which correspond to the modern transnational character of the anti-social phenomenon of corruption. It was found that most of the tasks to be achieved by anti-corruption courts have not been fully achieved. It has been proven that the effectiveness of these courts depends on a number of objective and subjective factors and the creation of specialized anti-corruption courts cannot be considered as a complete panacea for corruption. Perspective directions of further theoretical and practical researches are determined. The article formulates and solves a topical scientific problem in the field of public administration, which is to study and summarize the administrative and legal framework for the organization of anti-corruption courts in foreign countries in comparison with the relevant experience of Ukraine. These provisions and the results of this research serve as a basis for further theoretical and practical study of the principles of organization of anti-corruption courts in the world.